Preparation and in vitro screening of symmetrical bispyridinium cholinesterase inhibitors bearing different connecting linkage-initial study for Myasthenia gravis implications - Musilek, Kamil; Komloova, Marketa; Zavadova, Vlasta; Holas, Ondrej; Hrabinova, Martina; Pohanka, Miroslav; Dohnal, Vlastimil; Nachon, Florian; Dolezal, Martin; Kuca, Kamil; Jung, Young-Sik (Bioorganic & medicinal chemistry letters, 2010)
Reversible inhibitors (e.g., pyridostigmine bromide, neostigmine bromide) of carbamate origin are used in the early treatment of Myasthenia gravis (MG) to block acetylcholinesterase (AChE) native function and conserve efficient amount of acetylcholine for decreasing number of nicotinic receptors. Carbamate inhibitors are known for many undesirable side effects related to the reversible inhibition of AChE. In contrast, this paper describes 20 newly prepared bispyridinium inhibitors of potential concern for MG. Although some compounds from this series have been known before, they were not assayed for cholinesterase inhibition yet. The newly prepared compounds were evaluated in vitro on human erythrocyte AChE and human plasmatic butyrylcholinesterase (BChE). Their inhibitory ability was expressed as IC(50) and compared to standard carbamate drugs. Three compounds presented promising inhibition (in muM range) of both enzymes in vitro similar to the used standards. The novel inhibitors did not present selectivity between AChE and BChE. Two newly prepared compounds were chosen for docking studies and confirmed apparent pi-pi or pi-cationic interactions aside enzyme's catalytic sites. The kinetics assay confirmed non-competitive inhibition of AChE by two best newly prepared compounds.
Keywords: Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; karbamáty; Kinetics; vazebná místa; počítačová simulace; myasthenia gravis; Pyridinium Compounds; Structure-Activity Relationship; pyridinové sloučeniny; lidé; Myasthenia Gravis; Computer Simulation; katalytická doména; Carbamates; acetylcholinesterasa; vztahy mezi strukturou a aktivitou; cholinesterasové inhibitory; Cholinesterase Inhibitors; kinetika; Catalytic Domain; Binding Sites; Humans